Museum Sebagai Wisata dan Media Pendidikan Non-Formal Dalam Perspektif Pariwisata dan Pendidikan - Nur Laili, Veny; Santoso, Joko; Tjahja, Darmansjah (Rifa'Institute, 2024)
Attention to the existence of museums in Indonesia has shown positive results. Various types of museums accompanied by activities to involve the public in visiting museums have been promoted. Despite the fact that visitors have to queue to enter the museum, have to pay, and then it takes quite a long time to explore the entire collection and the museum's display system. Most people think that museums are always synonymous with ancient and antique things, with rooms that are dark, dusty and tend to be unkempt. This opinion may be true, because in reality many museums in Indonesia are poorly maintained, only functioning as collection rooms, so they become very uninteresting objects to visit. On the other hand, there is an opinion that a museum is a strategic institution that functions as a place for storing, caring for, safeguarding and utilizing objects, evidence and materials resulting from human culture which are useful for efforts to preserve the nation's cultural wealth.